صورة الممدوح في شعرإبن نباتة: The Depiction of Praiseworthy in the Poetry of Ibn-e-Nabatah - Dr. Muhammad Nasir Mustafa (Al Manhal Research Journal, 2024)
Praise, as the Arabs were accustomed, was only a mean to reach the highest ranks among the caliphs, princes, and ministers, and to gain gifts and obtain whatever money, gold, and housing they desired. As for praising Ibn-e-Nabatah, it was not out of seeking positions, but rather it was a pursuit of the nation’s glory that was lost in the mire of division. The man appeared clearly in Ibn-e-Nabatah’s poetry through his praise, as he demonstrated all of his qualities of courage, generosity and chivalry etc. He praised a number of princes and ministers, each of whom had qualities that distinguished him. Ibn-e-Nabatah was aware of this, so he painted pictures of praiseworthy, including the caliphs, princes, and ministers, characterized by exaggeration and glorification of their status, as we will see - in this research - when we look at those praised by the caliphs, ministers, and princes. This research relies on the Abstract, the life of Ibn-e- Nabatah, the image of the praiseworthy in his poetry, the conclusion of the research, and the indexes.